Meningkatkan Perkembangan Motorik Halus Melalui Kegiatan Mewarnai Kelompok B RA Al Muhsinin - Nuraliah Nuraliah; Joni Tesmanto (Neolectura, 2021)
Early childhood education aims to help the growth and development of children as early as possible. One that is developed in early childhood education is motor skills. The development of children's motor skills is divided into two, namely the development of soft motorics skills and the development of gross motor skills. These skills can be developed and improved through coloring activities. However, the field says otherwise. Therefore, this study aims to determine whether coloring activities can improve the soft motorics skills of children in group B of RA Al Muhsinin, South Tambun District. This research is a collaborative classroom action research. This research was conducted in RA Al Muhsinin, South Tambun District. The selection of this location was done because in that class there were problems with the children's soft motorics skills related to soft motorics skills. The subjects in this study were children of group B RA Al Muhsinin, South Tambun District, totaling 12 children, consisting of 4 boys and 8 girls. The object of this research is soft motorics skills. The CAR model used consists of four components, namely plans, actions and observations and reflections. Data collection techniques used in this study are observation and documentation. The data analysis technique used a qualitative and quantitative descriptive approach. The results showed that coloring activities could improve the soft motorics skills of children in group B of RA Al Muhsinin, South Tambun District.